Determinan Kecenderungan Kecurangan pada Pengelolaan Keuangan Dana Desa (Studi Kasus pada Desa di Kabupaten Buleleng) - Kadek Aniasih; Desak Nyoman Sri Werastuti (Universitas Pendidikan Ganesha, 2022)
This study aims to determine the effect of organizational commitment, internal control, and organizational ethical culture on the tendency of accounting fraud (fraud) in the Village Fund Financial Management in Buleleng Regency. This type of research is quantitative research. The population used is all village apparatus consisting of village heads, village secretaries, village treasurers and BPD chair in Buleleng Regency. The sampling technique in this study used the Slovin method. By using a sample of 224 respondents. The data source used is primary data. Data obtained from distributing questionnaires directly to respondents. Data analysis in this research uses descriptive analysis, data quality test, classic assumption test, multiple linear regression analysis and hypothesis testing with the help of SPSS version 23.0. The results showed that 1) organizational commitment had a negative and significant effect on trends in accounting fraud, 2) internal control had a negative and significant effect on trends in accounting fraud; and 3) organizational ethical culture has a negative and significant effect on trends in accounting fraud.